Espacios de emancipación, propuestas indígenas desde el Ecuador - Soriano Hernández, Silvia (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
The indigenous presence in Ecuador is not confined to street demonstrations. From local to national, organized Indians have made proposals that they hope will affect decisions that are taken without consulting them. In order to reflect and appreciate their approaches, I will make a brief tour of the image they express of the nation as a representation, without neglecting the question of racism. I am interested in questioning the idea of modernity as alien to indigenous people, to consider the democracy that characterizes our societies is exclusionary and, finally, approach female militancy to understand the opinions expressed by those who feel a fundamental part of a political structure such as the CONAIE.

La presencia indígena en Ecuador no se circunscribe a las manifestaciones en las calles. Desde lo local hasta lo nacional, los indios organizados han hecho propuestas que esperan incidan en las decisiones que se toman sin consultarles. Para reflexionar y valorar sus planteamientos, daré un breve recorrido por la imagen que expresan de la nación como representación, sin dejar de lado la cuestión del racismo. Me interesa cuestionar la idea de la modernidad como ajena a los indígenas, para considerar la democracia que caracteriza a nuestras sociedades como excluyente y cerrar con la militancia femenina para entender las opiniones formuladas por quienes se sienten parte fundamental de una estructura política como lo es la CONAIE.
Emancipatory spaces, indigenous proposals from Ecuador
Keywords: Organización; Democracia; Racismo; Género; https://purl.org/pe-repo/ocde/ford#5.04.00